Working Beyond the Normal Retirement Age in Urban China and Urban Russia - Björn Anders Gustafsson; Ludmila Nivorozhkina; Haiyuan Wan (Institute of Labor Economics (IZA), 2021)
The incidence of working for earnings beyond the normal pension age of 55 for females and 60 for males in urban China and Russia is investigated using micro-data for 2002, 2013, and 2018. Estimated logit models show that, in both countries, the probability of working after normal retirement age is positively related to living with a spouse only, being healthy, and having a higher education level but is negatively associated with age, the scale of pension and, in urban China, being female. We find that seniors in urban Russia are more likely to work for earnings than their counterparts in China. Two possible reasons for this difference are ruled out: cross-country differences in health status and the age distribution among elderly people. We also show that working beyond the normal retirement age has a much stronger negative association with earnings in urban China than in urban Russia. This is consistent with the facts that the normal retirement age is strictly enforced in urban China and seniors attempting to work face intensive competition from younger migrant workers. We conclude that China can learn from Russia that it has a substantial potential for increasing employment among healthy people under 70.
Keywords: E24; J14; J; 26; J3; P52; 330; retirement; older people; employment; China; Russia; labour market